Regularity of “F ” method of summability of sequences - Yu Chuen Wei (International Journal of Mathematics and Mathematical Sciences)
This paper is to develop theorems concerning the REGULARITY of the method “F” which is more general than Cesaro's, Able's and Riemann's methods In the theory of summabillty.